Pleiotropic effects of nutritional ketosis: Conceptual framework for keto-adaptation as a breast cancer therapy. (2017) - Hyde, Parker N.; Lustberg, Maryam B.; Miller, Vincent J.; LaFountain, Richard A.; Volek, Jeff S.
Abstract: There currently exists a lack of consensus regarding optimal nutrition strategies for cancer survivors underscoring the need for well-controlled dietary intervention studies investigating promising approaches. Several days of dietary carbohydrate restriction to levels < 40–50 g/day, with moderate protein, results in increased circulating beta-hydroxybutyrate (BOHB) by an order of magnitude. When maintained for several consecutive weeks, the metabolic state of ' nutritional ketosis ' awakens a dormant set of genes and metabolic programs that counteract insulin resistance and manifest in several positive health outcomes. This process, referred to as ' keto-adaptation ', is characterized by accelerated rates of whole body fatty acid oxidation, while glycolysis, insulin concentrations, insulin receptor activation and signaling, constitutive inflammation and oxidative stress are all decreased. Interest in nutritional ketosis as a therapeutic approach in various cancer models, as well as many other disease states, is burgeoning. In humans, the majority of ketosis-related cancer work has focused on head/neck cancers and glioblastoma multiforme due to the elevated Warburg Effect demonstrated. Although breast cancer is a heterogeneous disease, some of the most common tumorigenic and metastatic pathways frequently exhibited are targeted by keto-adaptation. Many of the phenotypic outcomes associated with keto-adaptation relate directly or indirectly to breast cancer pathologies and comorbidities. In this review we discuss the rationale for nutritional ketosis as a pleiotropic treatment modality relevant to breast cancer, and the potential for keto-adaptation to serve as an adjunct or standalone therapy in breast cancer.